Posterior Approach and Spinal Cord Release for 360° Repair of Dural Defects in Spontaneous Intracranial Hypotension. Issue 6 (25th July 2018) - Beck, Jürgen; Raabe, Andreas; Schievink, Wouter I; Fung, Christian; Gralla, Jan; Piechowiak, Eike; Seidel, Kathleen; Ulrich, Christian T
Abstract: BACKGROUND: Spinal cerebrospinal fluid (CSF) leaks are the cause of spontaneous intracranial hypotension (SIH). OBJECTIVE: To propose a surgical strategy, stratified according to anatomic location of the leak, for sealing all CSF leaks around the 360° circumference of the dura through a single tailored posterior approach. METHODS: All consecutive SIH patients undergoing spinal surgery were included. The anatomic site of the leak was exactly localized. We used a tailored hemilaminotomy and intraoperative neurophysiological monitoring (IOM) for all cases. Neurological status was assessed before and up to 90 d after surgery. RESULTS: Forty-seven SIH patients had an identified CSF leak between the levels C6 and L1. Leaks, anterior to the spinal cord, were approached by a transdural trajectory (n = 28). Leaks lateral to the spinal cord by a direct extradural trajectory (n = 17) and foraminal leaks by a foraminal microsurgical trajectory (n = 2). The transdural trajectory necessitated cutting the dentate ligament accompanied by elevation and rotation of the spinal cord under continuous neuromonitoring (spinal cord release maneuver, SCRM). Four patients had transient defiticts, none had permanent neurological deficits. We propose an anatomic classification of CSF leaks into I ventral (77%, anterior dural sac), II lateral (19%, including nerve root exit, lateral, and dorsal dural sac), and III foraminal (4%). CONCLUSION: Safe sealing (with IOM) of all CSF leaks around the 360° surface of the dura is feasible through a single posterior approach. The exact surgical trajectory is selected according to the anatomic category of the leak.